Predicting the Stock Prices of Private Banks through Technical Analysis Indicators and Supply Chain Management - Sallal Rahi AL-Hisnawi, Salim; Abd AL-Shara, Aqeel Shakir; Al – Bidairi, Karrar Hatam Attieh (International Journal of Supply Chain Management, 2018)
Abstract- The aim of the research is identifying the extent of using the Iraqi investors from the stock exchange and the technical analysis by understanding the extent knowledge of the investor for dependence on taking investment decisions to enter or exit from the market. To prove the hypothesis of research, some companies in the bank sector listed in the Iraqi Stock Exchange were selected to be a research community, as a sample was selected composed of six banks to be a field of research. The research was based on a set of analysis indicator and supply chain management used in the forecasting process towards stock prices by (Simple average, rate of change, momentum, relative strength) in addition to some statistical tests such as Livens test, T test and F test according to the statistical program SPSS 20. The research reached that revolve around the existence of the statistical significance of the reliability of these indicators in the process of forecasting towards stock prices for the banking sector companies listed in the Iraq Stock Exchange to suit the Iraq environment conditions.    Keywords: Technical Analysis, investment, Rate of change, Momentum, Relative Strength.